Transparency Triumphs: Unraveling the Impact of Village Fund Management Accountability and Policies on Rural Prosperity - Rojak, Jeje Abdul; Issalillah, Fayola (Bulletin of Science, Technology and Society, 2022)
With the existence of the Village Fund Allocation, the village has the authority to regulate and manage its household in accordance with the authority given, which involves the role of the village government as the organizer of public services in the village and as a goal in the process of planning and implementing regional development involving the community at the village level. In carrying out this authority, the village government has revenue resources that are used to finance activities carried out in the village, and this is also based on village policy. This study aims to determine the role of accountability in the management of village fund allocations and village policies for the welfare of villagers. This type of research is quantitative, involving a total of 180 respondents taken according to the purposive sampling technique. The type of data includes primary data obtained through the distribution of questionnaires. This research uses quantitative descriptive analysis, instrument tests, classical assumption tests, multiple linear regression tests, and hypothesis testing. This research was assisted by the SPSS 26 program to process the data. The results of the analysis of 180 people as respondents using multiple linear regression analysis The results showed that the accountability variable of village fund allocation management played a significant role in the welfare of villagers, and the village policy variable played a significant role in the welfare of villagers. For this reason, all hypotheses in the study were accepted.